2011
DOI: 10.17221/3262-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Development of isogenic lines for resistance to Septoria tritici blotch in wheat

Abstract: Septoria tritici blotch (STB), caused by the fungus Mycosphaerella graminicola (asexual stage: Septoria tritici), is one of the most economically important diseases of wheat worldwide. During the past decade 13 genes for resistance to STB have been identified and several molecular markers have been developed. However, analysis of resistance gene expression and utility for plant improvement programs would be increased if the resistance genes were isolated in a common susceptible background. To address this prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…Although the different mapping methods, marker systems, and populations used can make it difficult to compare QTL positions from different studies, some of the QTLs detected in this analysis coincided with the mapping positions of previously reported major STB resistance genes. Hence, the putative QTL on 1B (qSTB.04) may represent Stb2 (Liu et al, 2013) and/or Stb11 (Chartrain et al, 2009), the QTLs on 1D (qSTB.05-07) may represent Stb10 (Chartrain et al, 2005), the QTL on 2B may represent Stb9 (Chartrain et al, 2009), the QTLs on 3A (qSTB.15-17) may represent Stb6 (Brading et al, 2002) and/or StbSm3 (Cuthbert, 2011), the QTLs on 3B may represent Stb14 (Cowling, 2006), the QTLs on 3D may represent Stb16q (Tabib Ghaffary et al, 2012), the QTL on 4A may represent Stb7 (McCartney et al, 2003) or Stb12 (Chartrain et al, 2005), the QTLs on 5A may represent Stb17 (Tabib Ghaffary et al, 2012), the QTLs on 5B may represent Stb1 (Adhikari et al, 2004a), the QTL on 6A may represent Stb15 (Arraiano et al, 2007), the QTLs on 7A may represent Stb3 (Goodwin and Thompson, 2011) or TmStb1 (Jing et al, 2008), the QTL on 7B may represent Stb8 (Adhikari et al, 2003) or Stb13 (Cowling, 2006), and the putative QTLs on 7D may represent Stb4 (Adhikari et al, 2004b) or Stb5 (Arraiano et al, 2001). Similar to the results of this study, Kollers et al (2013) also reported significant MTAs for STB resistance on chromosomes 2A and 2D.…”
Section: Discussionmentioning
confidence: 99%
“…Although the different mapping methods, marker systems, and populations used can make it difficult to compare QTL positions from different studies, some of the QTLs detected in this analysis coincided with the mapping positions of previously reported major STB resistance genes. Hence, the putative QTL on 1B (qSTB.04) may represent Stb2 (Liu et al, 2013) and/or Stb11 (Chartrain et al, 2009), the QTLs on 1D (qSTB.05-07) may represent Stb10 (Chartrain et al, 2005), the QTL on 2B may represent Stb9 (Chartrain et al, 2009), the QTLs on 3A (qSTB.15-17) may represent Stb6 (Brading et al, 2002) and/or StbSm3 (Cuthbert, 2011), the QTLs on 3B may represent Stb14 (Cowling, 2006), the QTLs on 3D may represent Stb16q (Tabib Ghaffary et al, 2012), the QTL on 4A may represent Stb7 (McCartney et al, 2003) or Stb12 (Chartrain et al, 2005), the QTLs on 5A may represent Stb17 (Tabib Ghaffary et al, 2012), the QTLs on 5B may represent Stb1 (Adhikari et al, 2004a), the QTL on 6A may represent Stb15 (Arraiano et al, 2007), the QTLs on 7A may represent Stb3 (Goodwin and Thompson, 2011) or TmStb1 (Jing et al, 2008), the QTL on 7B may represent Stb8 (Adhikari et al, 2003) or Stb13 (Cowling, 2006), and the putative QTLs on 7D may represent Stb4 (Adhikari et al, 2004b) or Stb5 (Arraiano et al, 2001). Similar to the results of this study, Kollers et al (2013) also reported significant MTAs for STB resistance on chromosomes 2A and 2D.…”
Section: Discussionmentioning
confidence: 99%
“…Stb1 , Stb2 and Stb3 have been mapped to chromosome arms 5BL (i.e. the long arm of chromosome 5B; Adhikari et al, 2004a ), 1BS (the short arm of 1B; Liu et al, 2013 ) and 7AS ( Goodwin and Thompson, 2011 ) respectively. Stb2 and Stb3 were originally mapped to chromosomes 3BS and 6DS respectively ( Adhikari et al, 2004b ) but those locations were corrected for the reasons given in the subsequent papers.…”
Section: Qualitative Resistancementioning
confidence: 99%
“…The wheat resistance against Z. tritici is controlled by (i) gene-for-gene relationships leading to incompatible interactions (Brading et al, 2002) and/or by (ii) non-specific and partial resistance expressed during compatible interactions (Chartrain et al, 2004a). While Z. tritici is able to overcome specific resistance controlled by one of the 18 known stb wheat genes (Goodwin, 2007;Goodwin and Thompson, 2011;Simón et al, 2012), partial resistance, controlled by several quantitative trait loci (QTL), is more durable at the field level (Orton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%